Multi-Laboratory Validation of a Loop-Mediated Isothermal Amplification Method for Screening Salmonella in Animal Food - Ge, Beilei; Domesle, Kelly J.; Yang, Qianru; Hammack, Thomas S.; Wang, Shizhen S.; Deng, Xiaohong; Hu, Lijun; Zhang, Guodong; Hu, Yuan; Lai, Xiaokuang; Chou, Kyson X.; Dollete, Jan Ryan; et al. (Frontiers in Microbiology, 2019)
Loop-mediated isothermal amplification (LAMP) has gained wide popularity in the detection of Salmonella in foods owing to its simplicity, rapidity, and robustness. This multi-laboratory validation (MLV) study aimed to validate a Salmonella LAMP-based method against the U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) Chapter 5 Salmonella reference method in a representative animal food matrix (dry dog food). Fourteen independent collaborators from seven laboratories in the U.S. and Canada participated in the study. Each collaborator received two sets of 24 blind-coded dry dog food samples (8 uninoculated; 8 inoculated at a low level, 0.65 MPN/25 g; and 8 inoculated at a high level, 3.01 MPN/25 g) and initiated the testing on the same day. The MLV study used an unpaired design where different test portions were analyzed by the LAMP and BAM methods using different preenrichment protocols (buffered peptone water for LAMP and lactose broth for BAM). All LAMP samples were confirmed by culture using the BAM method. BAM samples were also tested by LAMP following lactose broth preenrichment (paired samples). Statistical analysis was carried out by the probability of detection (POD) per AOAC guidelines and by a random intercept logistic regression model. Overall, no significant differences in POD between the Salmonella LAMP and BAM methods were observed with either unpaired or paired samples, indicating the methods were comparable. LAMP testing following preenrichment in buffered peptone water or lactose broth also resulted in insignificant POD differences (P > 0.05). The MLV study strongly supports the utility and applicability of this rapid and reliable LAMP method in routine regulatory screening of Salmonella in animal food.